REDUCING HOMESICKNESS USING SOLUTION-FOCUSED BRIEF COUNSELING - Hasanah Hasanah (Study Program Guidance and Counseling, Univesitas Pendidik, 2024)
Based on the results of the questionnaire data as many as 67.5% or 79 out of 117 students in class VII girls still experience homesickness. Referring to the background that has been stated above, the follow-up action taken by the counseling teacher is to conduct group counseling services with SFBC (solution focus brief counseling) techniques to reduce homesickness in students. The purpose of this study is first to find out the process of applying SFBC (solution-focused brief counseling) counseling techniques in reducing homesickness, and second to find out the application of SFBC (solution-focused brief counseling) counseling techniques in reducing homesickness in students. The type of research conducted uses class action research. Classroom action research conducted by design refers to the Kemmis Taggart model design, where each cycle in this study consists of four stages, namely, (1) planning, (2) action, (3) observation, and (4) reflection. The research was conducted with two cycles, the results of the first cycle research are From the results of data processing cycle 1 (after group counseling services with SFBC techniques) it is known that there are 13% or 3 students in the high homesickness category, and 88% or 21 students in the very high homesickness category. The results of the Guidance and Counselling Action research in cycle two, namely the results obtained that as many as 25% or 6 students were classified into the high homesickness category, and as many as 75% or 18 students were classified into the very high homesickness category. Here there is an increase in percentage from 13% to 25% for the high category and a decrease in percentage from 88% to 75% in the very high homesickness category. Then there is an increase in the comfort scale from cycle 1 to cycle 2 by 20 people. Keywords: Homesickness, Counseling, Solution-Focused